The Birth of a Connected South Atlantic Ocean: A Magnetostratigraphic Perspective - Palcu, Dan V.; Muraszko, Joy R.; Jaqueto, Plinio F.; Jovane, Luigi (Frontiers in Earth Science, 2020)
The early Paleogene sedimentary record of the Sao Paulo Plateau holds the key to understanding the timing and mechanisms of the onset of Atlantic oceanic circulation, with implications for ocean - climate feedback systems. The timing and evolution of South Atlantic Ocean connectivity remain poorly understood, hindering a full understanding of modern circulation mechanisms. In this work, we develop an improved magnetostratigraphic age model for the late- Cretaceous to Eocene sedimentary record of Deep-Sea Drilling Project (DSDP) Site 356, located on the São Paulo Plateau at the edge of the Rio Grande Rise. The model constrains the timing of the beginning of Atlantic Ocean circulation, as the last obstacle to a connected Atlantic was removed. We use the age model to quantify sedimentary rates, and correlate with rock magnetic and published geochemical data to explore links between ocean current rearrangement and climatic anomalies. We find that periods characterized by variations in the magnetic properties of sediments and sedimentation anomalies in the Sao Paulo Plateau are reflected in carbon isotope events, supporting a possible link between ocean circulation and hyperthermal events.